Humanization and playfulness in children’s oncology treatment wards: design recommendations for environments - Aredes, Camila Lima; Castro, Iara Sousa (DAT Journal, 2024)
The theme of this article approaches humanization and playfulness applicable to children’s oncology environments. The objective is to develop design guidelines aimed at humanization and playfulness so that environmental designers can apply those in pediatric ward designs of oncology hospitals. A qualitative and exploratory nature methodology was organized into stages of bibliographic review, documental analysis, data collection made through a questionnaire and the visual selection, analysis and discussion of the collected data. Results present design recommendations, arising from humanization focused on ergonomics, layout, comfort, lighting, landscaping and the medical team training, in addition to recommendations, arising from playfulness related to the use of colors and the creation of spaces for socialization. The conclusion highlights the relevance of intangible elements in pediatric hospital spaces, standing out the importance of considering humanization and playfulness in the design of children’s oncology environments.